Tinjauan Yuridis Akibat Hukum Perceraian dalam Memperoleh Hak Asuh Anak dalam Perkawinan di Bawah Tangan - Ivana Theo Philia; Reylan Silverius Sinaga; Dules Ery Pratama; Jojor Mindo Manullang; Ture Ayu Situmeang (Departement of Mathematics Education, 2024)
Marriage is a legal relationship in society which is an inner bond between a man and a woman as husband and wife to form a family (household), happy and eternal based on the belief in the Almighty God. Marriage is a very important thing in human life, both for individuals and groups. One of the initial frameworks for obtaining legal guarantees in a marriage is to register it with the authorized agency. A private marriage or invalid marriage is a marriage that is not registered at the civil registry office, but fulfills the basic pillars and requirements of marriage according to Islamic law. The legal consequence of divorce in obtaining private child custody according to western civil law is that the marriage does not disappear from child custody obligations. The aim of this research is to find out how to obtain and the legal consequences of child custody under western civil law. This research uses a normative juridical legal research method, a qualitative approach with a normative juridical research type. Data collection techniques through journal and book data sources regarding Juridical Review of the Legal Consequences of Divorce in Obtaining Child Custody in Underhand Marriages.